Ammonia removal from simulated fish farms by metal organic framework ingrained by egg shell and fish bones - Ebtehal A. H. Gamal; Reda M. Abdelhameed; Hossam E. Emam; Hanan B. Ahmed (Scientific Reports)
Abstract The current work focuses on the efficient removal of ammonia by calcium-based metal organic framework. Whereas, for the first time, Ca based metal organic framework was synthesized using either fish bones (FB) or eggshell (ES) as biogenic wastes to act as calcium precursors for synthesis of Ca-BDC, abbreviated as Ca-BDC(FB) & Ca-BDC(ES), respectively, to be sequentially applicable for removal of ammonia. The collected data revealed that; FB showed to be more preferable rather than ES as calcium precursor for preparation of highly efficient Ca-BDC. The obtained Ca-BDC (ES) and Ca-BDC (FB) were shown with orthorhombic crystals, while smaller crystal size was observed in case of Ca-BDC (FB) which is reflected in larger surface area (721.38 m2/g) and in turn higher absorptivity for more efficient removal of ammonia. The adsorption of ammonia followed the pseudo-second ordered reaction and Langmuir isotherm, also R2 values of second ordered and Langmuir models were estimated to be 0.98 & 0.99 for Ca-BDC (ES) & Ca-BDC (FB), respectively. The evaluated maximum adsorption capacities (Qm) onto ES & Ca-BDC (ES) were 86.99 mg/g and 308.16 mg/g, respectively. The maximum capacities of ammonia onto FB & Ca-BDC (FB) were 184.28 mg/g and 616.11 mg/g, respectively. Whereas, Ca-BDC (FB) (721.38 m2/g) was shown with significantly wider surface area by factor of 1.3 compared to Ca-BDC (ES) (563.16 m2/g). Overall, the study provides a promising trend for in designing MOFs with appropriate central metals for capturing of NH3.